Local Government Plan Formulation Process in Federalism - Bhattarai, Nabaraj (Academic View, Journal of TUTA Tri-Chandra Campus Unit, 2023)
It has been more than 7 decades since planned development started in Nepal. Meanwhile, 10 five-year plans and 5 three-year plans have been implemented. Despite the implementation of so many plans, the people's expectations could not be fully realized. Although some economic and social foundations have been built during this period, the people have not been able to feel the development as expected. In the 21st century, the plan has gained great importance such as achieving sustainable economic development, reducing unemployment ,alleviating poverty, and maintaining regional balance. At first it was considered as an economic program of a communist country, due to the economic recession, all developed and developing capitalist countries felt the need for economic planning. After the said recession, the construction and implementation of plans started in different ways in almost all countries, In a busy sense, the population consist of the knowledge, skill, creativity, attitude and talent of the people in a nation. Based on this concept of population the plan is formulated, and the foundation stone of local level capacity development is also built.